DIVINE AND DISADVANTAGED: EXPLORING THE THEYYAM PERFORMERS OF NORTH MALABAR - Anthappai, Teddy C. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Caste and caste inequalities continue to be a significant reality in contemporary society, even in Kerala, where high levels of development, literacy, and secularism coexist. Despite these advancements, caste remains a critical factor in the social and cultural lives of the people. The caste system within Hinduism is characterized by a hierarchy that perpetuates disparities in power and wealth, as well as imbalances in religious practices. This study conducts an ethnographic investigation into the renowned religious ritual of Kaliyattam in Northern Kerala, revealing the harsh realities of caste dynamics, ritual authority, and exploitation present in society. Various communities involved in the ritual are required to adhere to strict customs that often result in economic exploitation and social injustice. These customs reflect the ongoing inequalities that persist within the caste system, highlighting the need for a deeper understanding of how these issues manifest in both ritual contexts and broader societal interactions.